2022
DOI: 10.1002/cncy.22628
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of p16/Ki‐67 dual‐stain as triage test for high‐risk HPV‐positive women: A hospital‐based cross‐sectional study

Abstract: BACKGROUND: Most human papillomavirus (HPV)-positive women recover from infections and do not develop cervical intraepithelial neoplasia (CIN) and cervical cancer. Additional triage approaches are needed to reduce unnecessary colposcopy referrals. The aim of this study is to determine the high-risk HPV prevalence in a hospital-based population and to evaluate the performance of p16/Ki-67 dual-stain test for the triage of high-risk HPV-positive women to detect precursor lesions and cervical cancer compared with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…Previous studies have shown that p16/Ki-67 double staining has a sensitivity of 91.6% and specificity of 95.0% in detecting VAINII + [ 35 ]. Boonlikit et al found that compared to cytology screening, p16/Ki-67 double staining can be an effective triage strategy for HR-HPV-positive women [ 36 ].…”
Section: Auxiliary Examination and Diagnostic Methodsmentioning
confidence: 99%
“…Previous studies have shown that p16/Ki-67 double staining has a sensitivity of 91.6% and specificity of 95.0% in detecting VAINII + [ 35 ]. Boonlikit et al found that compared to cytology screening, p16/Ki-67 double staining can be an effective triage strategy for HR-HPV-positive women [ 36 ].…”
Section: Auxiliary Examination and Diagnostic Methodsmentioning
confidence: 99%
“…Elevated Ki-67 levels in cervical cells suggest a higher rate of cell turnover, which is a characteristic of both dysplastic and neoplastic processes. Therefore, Ki-67 staining is often used in conjunction with other histopathological and cytological evaluations to assess the severity of cervical lesions [57,58]. In cervical cancer screening and management, Ki-67 can serve as an adjunct marker to improve the accuracy of cytological diagnosis.…”
Section: P16/ki-67 Dual Staining: An Emerging Tool For Triagementioning
confidence: 99%
“…Dual staining for p16 and Ki-67 is particularly useful in cervical cancer screening because these two proteins are mutually exclusive in normal cells [56,61,62]. Therefore, their co-expression serves as a specific marker for HPV-mediated oncogenic transformation and indicates a higher risk of cervical cancer [58,63]. This method helps differentiate between transient, harmless HPV infections and persistent infections with a higher potential to progress to high-grade pre-cancer or invasive carcinoma.…”
Section: P16/ki-67 Dual Staining: An Emerging Tool For Triagementioning
confidence: 99%